Herpes-Associated Erythema Multiforme Following SARS-CoV-2 Infection in a Vaccinated Young Woman - Erna Sulistyani (Faculty of Dentistry, Universitas Trisakti, 2023)
Background: Patients with SARS-CoV-2 infection often exhibit diverse oral manifestations, necessitating a dentist’s familiarity with identification and treatment. Case Report: This paper presents a case involving a 23-year-old woman with erythema multiforme on her lips, scalp, and fingers following SARS-CoV-2 infection. The aim of this case report is to disseminate information on oral manifestations following COVID-19. The patient, vaccinated thrice with a booster, initially experienced gum and lip edema with easy bleeding during fever. The condition was confirmed by self-captured images. On the first visit, two days after the antigen test swab was negative, a thick black-yellow crusted lesion on the lips and an itchy lesion on the finger and scalp were observed. Blood tests revealed positive anti-Herpes Simplex Virus IgG, elevated lymphocytes, and increased Erythrocyte Sedimentation Rate, leading to a diagnosis of herpes-associated erythema multiforme. Treatment involved topical application of betamethasone and neomycin ointment, supplemented by vitamin B complex, vitamin C, and zinc. Conclusion: The patient showed improvement in three days, with the lesion completely healed in seven days.